2015
DOI: 10.1111/ced.12703
|View full text |Cite
|
Sign up to set email alerts
|

Home phototherapy for psoriasis: a review and update

Abstract: A 2006 survey of dermatologists showed that home phototherapy should be used with caution, and that general, nonevidence-based opinions were widespread about this form of therapy. This led to a randomized controlled trial to assess the safety and efficacy of home phototherapy vs. outpatient phototherapy by the same authors in 2009, which concluded that a lower burden of treatment and increased patient satisfaction were associated with home phototherapy. In the UK National Health Service, with a single exceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…Bu alanda öncü bir çalışma olarak kabul edilebilecek PLUTO çalışmasında, psoriasis hastalarında evde uygulanan dar bant UVB tedavisinin, hastanede uygulanan fototerapi ile benzer etkinlikte olduğu ve benzer yan etki profiline sahip olduğu gösterilmiştir (113). İngiltere, Hollanda ve Amerika'da evde fototerapi uygulanması ile ilgili farklı düzenlemeler bulunmaktadır (114). İngiltere'de, evde fototerapi için kullanılacak fototerapi cihazları, merkez fototerapi ünitesinde tutulmaktadır.…”
Section: Psoriasiste Fototerapiunclassified
“…Bu alanda öncü bir çalışma olarak kabul edilebilecek PLUTO çalışmasında, psoriasis hastalarında evde uygulanan dar bant UVB tedavisinin, hastanede uygulanan fototerapi ile benzer etkinlikte olduğu ve benzer yan etki profiline sahip olduğu gösterilmiştir (113). İngiltere, Hollanda ve Amerika'da evde fototerapi uygulanması ile ilgili farklı düzenlemeler bulunmaktadır (114). İngiltere'de, evde fototerapi için kullanılacak fototerapi cihazları, merkez fototerapi ünitesinde tutulmaktadır.…”
Section: Psoriasiste Fototerapiunclassified
“…It can be used for all the conditions treated with phototherapy, although the single most frequent indication is psoriasis. Training and remote monitoring of patients are provided by expert phototherapy nurses . In recent years, home phototherapy has become more widely available around the world .…”
mentioning
confidence: 99%
“…Training and remote monitoring of patients are provided by expert phototherapy nurses . In recent years, home phototherapy has become more widely available around the world . A questionnaire survey in 2006 revealed that dermatologists in 33 countries expressed worries about the safety and efficacy of home phototherapy .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these (HB‐A and HB‐B) had existing phototherapy services located in hospitals in secondary care; the third (HB‐C) served a rural community with no current phototherapy services. Thus, two options for new phototherapy services were available: new fixed phototherapy hubs located in urban areas or home phototherapy, where patients treat themselves in their own homes . The location and number of new hospital‐based phototherapy hubs was identified as being a location analysis problem.…”
mentioning
confidence: 99%